Assessing the changes of the monetary value of mangrove ecosystem services in China and its application - Lin, Chun-Yu; Fu, Chen-Yang; Liu, Ying; Zhang, Meng-Qi; Liu, Yang; Wu, Wan-Yu; Wang, Li-Xia; Lin, Xiang-Hong; Fu, Xiu-Mei (Frontiers in Environmental Science, 2022)
With the development of marine economy and climate changing, the ecological value of mangrove ecosystem has become increasingly prominent. In this study, the ecological values of China's mangrove ecosystem services was evaluated based on the four services and nine functions of mangrove ecosystem. On this basis, the dynamic changing characteristics of the nine mangrove ecological values from 2001 to 2019 were analyzed. The results indicated that the top four service values were that of preventing coastal erosion, raw material supply, regulating water resources, and regulating climate & maintaining air quality. Significant changes were found in China’s mangrove areas which increased during 2001-2013 and decreased during 2013-2019, while the unit area value of mangrove ecosystem services generally showed an upward trend. Subsequently, the evaluation results were applied to mangrove asset management with balance sheets, ecological compensation standard determination, and carbon trading in blue carbon sink. Based on the above analysis, the corresponding countermeasures and suggestions were proposed for mangrove protection and value application to guide effective management on mangroves and further to realize a higher ecological value of mangrove ecosystem.